Selective separation, detection of zotepine and mass spectral characterization of degradants by LCâMS/MS/QTOF - M.V.N. Kumar Talluri; Naveen Reddy Kandimalla; Raju Bandu; Divya Chundi; Ramesh Marupaka; Ragampeta Srinivas (Elsevier, 2014)
A simple, precise, accurate stability-indicating gradient reversed-phase high-performance liquid chromatographic (RPâHPLC) method was developed for the quantitative determination of zotepine (ZTP) in bulk and pharmaceutical dosage forms in the presence of its degradation products (DPs). The method was developed using Phenomenex C18 column (250Â mmÃ4.6Â mm i.d., 5Â Âµm) with a mobile phase containing a gradient mixture of solvents, A (0.05% trifluoroacetic acid (TFA), pH=3.0) and B (acetonitrile). The eluted compounds were monitored at 254Â nm; the run time was within 20.0Â min, in which ZTP and its DPs were well separated, with a resolution of >1.5. The stress testing of ZTP was carried out under acidic, alkaline, neutral hydrolysis, oxidative, photolytic and thermal stress conditions. ZTP was found to degrade significantly in acidic, photolytic, thermal and oxidative stress conditions and remain stable in basic and neutral conditions. The developed method was validated with respect to specificity, linearity, limit of detection, limit of quantification, accuracy, precision and robustness as per ICH guidelines. This method was also suitable for the assay determination of ZTP in pharmaceutical dosage forms. The DPs were characterized by LCâMS/MS and their fragmentation pathways were proposed. Keywords: Zotepine, Stability-indicating RPâHPLC method, Characterization, ESI-Q-TOF-MS, Bulk drugs and formulations